Bipolar Radiofrequency-Assisted Liposuction for Cervical Contouring in Eastern Asians - Yen, ShihChun; Wang, JiGeng; Gao, Xiang; Zhu, QiuXuan; Song, CaiYing; Zhu, Fei (Aesthetic surgery journal. Open forum, 2023)
Abstract Background East Asian beauty standards uphold a V-shaped face and a long slender neck. Some patients are dissatisfied with the concurrent nonsurgical treatment and prefer limited downtime with minimally invasive procedures to achieve a natural skin-tightening outcome. The authors performed bipolar radiofrequency-assisted liposuction (RFAL) to achieve cervical rejuvenation. Objectives To evaluate the efficacy and safety of RFAL for the treatment of cervical skin and soft-tissue laxity in Eastern Asians. Methods In total, 66 patients with neck skin and soft-tissue laxity were treated with bipolar RFAL under tumescent local anesthesia. Further, the surgical outcomes were evaluated based on patient satisfaction score and the Global Aesthetic Improvement Scale (GAIS) score at 6 months postoperatively. Moreover, the incidence of postoperative complications was determined. Results All patients were followed up for at least 6 months. After RFAL technologies treatment, significant improvement in the neck contour was observed. The average GAIS score was 3.03 (4, very much improved; 3, much improved; 2, improved; 1, no change; and 0, worsened). Approximately 93% of patients were satisfied with the RFAL neck contouring outcome. Notably, no serious complications requiring further intervention were encountered in this series. Conclusions The described RFAL treatment significantly improved the refinement of neck contouring in Eastern Asian subjects. The simple, minimally invasive cervical procedure under local anesthesia improve the cervical-mental angle definition, tissue-tightening effect, face slimming, and the mandibular line. No serious adverse events except mild complications were reported. This treatment could achieve extraordinary results with a high safety profile. Level of Evidence: 4